Launching a CDMO in Brazil aiming to develop biopharmaceuticals for clinical trials - Ferreira Junior, Rui Seabra [UNESP]; Morales, Marcelo Marcos; Barretti, Pasqual [UNESP]; Barraviera, Benedito [UNESP] (FapUNIFESP (SciELO), 2022)
The innovation timeline is expensive, risky, competitive, time-consuming, and laborintensive. In order to overcome such challenges and optimize financial resources, pharmaceutical companies nowadays hire contract development and manufacturing organizations (CDMO) to help them. Based on the experience acquired first from the development of two biopharmaceuticals, the Heterologous Fibrin Sealant and the Apilic Antivenom, and more recently, during their respective clinical trials; the Center for the Study of Venoms and Venomous Animals (CEVAP) proposed to the Ministry of Health the creation of the first Brazilian CDMO. This groundbreaking venture will assist in converting a candidate molecule - from its discovery, proof of concept, product development, up to pilot batch production - into a product. The CDMO impact and legacy will be immense, offering service provision to the public and private sector by producing validated samples for clinical trials and academic training on translational research for those seeking a position in pharmaceutical industries and manufacturing platforms.
Keywords: Biopharmaceuticals; Contract development and manufacturing organizations (CDMO); Good manufacturing practices (GMP); Translational research Clinical trials